Geração descentralizada de energia fotovoltaica no estado do Rio Grande do Sul - Denardin, Matheus D'Ávila (2016)
The Brazilian energy matrix is recognized as one of the most sustainable in the world, because 41% of the energy generated come from renewable sources, having the hydroelectric as of higher contribution and of greatest potential for expansion. However, when compared to other countries, by itself, not is exempt from criticism and even ensures sustainability character, because the participation of renewable sources has been dropping at a rate of 1.55% per year. The energy matrix of Rio Grande do Sul, in turn, generates only 26.7% of energy come from renewable sources, reinforcing this demand for solutions. Thus, it is perfectly justified the implementation of actions of research, development and innovation, as grants for the establishment of government policies to support and encourage the generation of alternatives to ensure the sustainability of the energy supply required, with emphasis on decentralized generation of photovoltaics, the example of the invaluable success occurring in countries like Germany, USA and Japan. T his study aimed to propose guidelines for the formulation of government policies to encourage investments targeted to the decentralized generation of photovoltaic energy in Rio Grande do Sul. The study involved the characterization of the energy matrices of Brazil and the State of Rio Grande do Sul and the establishment of prerequisites, from the analysis of the policies deployed in Germany, USA and Japan, to support the proposition of strategies indicating Government policies to encourage decentralised gen eration of electricity, with the potential of print energy security and sustainability to the energy matrix of the State of Rio Grande do Sul.